Survey of Interest in Studying Physical Education Sports and Health of Public Elementary School Students 03 Sukodono - Muhammad Virgo Andretti; Eko Sudarmanto (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
There is a sense of interest that the students of SDN 03 Sukodono have, there are two supporting factors, the first is internal factors and the second is external factors. Internal factors, namely factors that come from the students themselves include physical and psychological factors such as a sense of comfort and pleasure when participating in the Sports and Health Physical Education learning, while external factors are factors that come from outside the student such as educators, family, friends, the environment that gives each other encouragement or motivation to students. The purpose of this study was to find out how much interest students are and how important sports learning is for students of SDN 03 Sukodono. the sample in class V and VI students was 50 students of SDN 03 Sukodono, class V was 33 students while class VI was 17 students. The results of this study show that the interest of SDN 03 Sukodono students in learning Sports and Health Physical Education is quite high. It is proven that 90% of SDN 03 Sukodono students like sports and health physical education learning, there are several indicators of the reasons why SDN 03 students like sports and health physical education learning, namely: the body becomes healthy and fit, refreshes the brain, and wants to excel in the field of sports. In addition, many students of SDN 03 Sukodono want to excel in sports.